(untitled) (Journal of Nepal Geological Society, 1998)
The paper deals with the computer program to calculate temperature (in °C) and pressure (in kbar) based on assemblages garnet-clinopyroxene-plagioclase-quartz, and following reactions: (a) 1/3 Pyrope + Hedenbergite = 1/3 Almandine + Diopside, (b) Anorthite + Diopside = 2/3 Grossularite + 1/3 Pyrope + Quartz, (c) Anorthite + Hedenbergite = 2/3 Grossularite + 1/3 Almandine + Quartz. The program is written in Microsoft Quick Basic for IBM XT/AT compatible machines running MS DOS Version 3.0 or higher. The user can acquire a copy of program by sending the author a 3.5"/5.25" DD/HD floppy diskette. The executable code of the computer program is MPET4.EXE.